2010
DOI: 10.1002/wrna.56
|View full text |Cite
|
Sign up to set email alerts
|

Control of poly(A) tail length

Abstract: Poly(A) tails have long been known as stable 3' modifications of eukaryotic mRNAs, added during nuclear pre-mRNA processing. It is now appreciated that this modification is much more diverse: A whole new family of poly(A) polymerases has been discovered, and poly(A) tails occur as transient destabilizing additions to a wide range of different RNA substrates. We review the field from the perspective of poly(A) tail length. Length control is important because (1) poly(A) tail shortening from a defined starting p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
241
2
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(261 citation statements)
references
References 138 publications
4
241
2
4
Order By: Relevance
“…Another example of this type of regulators is PABPN1. In addition to its well-characterized functions in polyadenylation and poly(A) tail length control (Eckmann et al 2011), PABPN1 has recently been shown to suppress the usage of proximal PAS globally . As mentioned earlier, proximal PASs tend to lack consensus PAS sequences, such as the AAUAAA hexamer.…”
Section: Insights From Global Studies Of Apamentioning
confidence: 99%
“…Another example of this type of regulators is PABPN1. In addition to its well-characterized functions in polyadenylation and poly(A) tail length control (Eckmann et al 2011), PABPN1 has recently been shown to suppress the usage of proximal PAS globally . As mentioned earlier, proximal PASs tend to lack consensus PAS sequences, such as the AAUAAA hexamer.…”
Section: Insights From Global Studies Of Apamentioning
confidence: 99%
“…In both animal and plant development, alternative 39 end cleavage sites are widely used to regulate gene expression by modulating the length of the poly(A) tails on mRNAs in the cytoplasm (Eckmann et al, 2011) to influence the stability, nuclear export, and translational efficiency of the mRNAs (Hunt, 2008).…”
Section: A Role For Mrna Maturating Complexes In the Regulation Of Dementioning
confidence: 99%
“…The poly(A) tail at the 39 untranslated region (UTR) is an essential feature of virtually all eukaryotic mRNAs that influences stability, nuclear export, and translational efficiency of the mRNA (Eckmann et al, 2011). It is synthesized after RNA polymerase II has transcribed past the cleavage and polyadenylation site and associated signal sequences.…”
mentioning
confidence: 99%
“…8.1c ¢ ). A crucial aspect of cytoPAPs is that, 8 Translational Control in the Caenorhabditis elegans Germ Line contrary to nuclear PAP, the enzyme lacks a predictable RNA-binding domain (Eckmann et al 2011 ) . They associate with mRNA targets via other mRNP components and, therefore, are also referred to as noncanonical poly(A) polymerases (Wang et al 2002 ) .…”
Section: Poly(a)-tail Length Controlmentioning
confidence: 99%